Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species - Lee, Chi-Feng; Beenen, Ron (Zootaxa, 2017)
The brachelytrous galerucine genus Shairella Chûjô is reviewed based on examination of 240 specimens. Five new species are described: S. cheni sp. nov., S. chungi sp. nov., S. guoi sp. nov., S. motienensis sp. nov., and S. tsoui sp. nov. The diversity and distribution of most of Shairella species are reflected on one major host plant - Clinopodium laxiflorum var. taiwanianum. Smaller compound eyes relative to otherwise similar galerucines are characteristic for Shairella and may be related to nocturnal behavior. The occurrence of a subapical white band on the antenna and its possible function is discussed.